Алгоритм построения закона функционирования формирователя эквивалентов (ФЭ) - Коваленко, С. Н. (ХНУРЭ, 2009)
In this work the algorithm of construction of functioning law of the equivalents former for parallel strategy using of convertion steps is considered.